Sistema imune artificial para o problema de escalonamento Job Shop - Ribeiro, Sildenir Alves (2006)
This work presents an Artificial Immune System (AIS) to deal with problems scheduling. The Artificial Immunologic System developed in this project was based on the structure, architecture and functioning of the Biological or Natural Immune Systems. The use of Genetic Algorithm (GA) became necessary to represent the antibodies and antigens of the AIS. Each individual generated for the GA represented a processed task set library in a set of machines. The evaluation of each individual was given by a fitness function that represents the process of natural selection. The evolution of the individuals, and population as a consequence was obtained by applying the genetic operators of crossover e mutation. The machines and the tasks used for the scheduling represent the problem of Job Shop Scheduling (JSS). Some classic tests of the literature where applied to the problem in order to verify the viability of the AIS on the treatment of task of scheduling problems. Those tests also demonstrated the system s behavior its entire execution, therefore, allowing for a detailed analysis of the system s functionalities sets for certain time period. The representation of the natural immunologic systems through computational algorithms inspires from all over world researchers. The motivation is that the immunologic systems possess parallelism characteristics adaptability and learning, which can be applied in several problems found in many areas, had its portability.